In vivo kinematic analysis of replaced hip during stationary cycling and computer simulation of optimal cup positioning against prosthetic impingement. (August 2019) - Komiyama, Keisuke; Hamai, Satoshi; Ikebe, Satoru; Yoshimoto, Kensei; Higaki, Hidehiko; Shiomoto, Kyohei; Gondo, Hirotaka; Hara, Daisuke; Wang, Yifeng; Nakashima, Yasuharu
Abstract: Background: Dynamic hip kinematics during stationary cycling after total hip arthroplasty (THA) have been unclear. Furthermore, no computer simulation of optimal cup position based on in vivo kinematics has yet been assessed. Methods: This study consisted of 7 patients who underwent unilateral primary THA for symptomatic osteoarthritis. Using a flat-panel X-ray detector, continuous radiographs were obtained during stationary cycling. We analyzed the three-dimensional replaced hip kinematics from the top to the bottom position of the crank using image-matching techniques and quantified minimum liner-to-stem neck distance. Simulation analyses with in vivo kinematics were performed to examine patient-specific optimal cup placement against prosthetic impingement. Findings: During stationary cycling, pelvis showed 27.1° of posterior tilt on average without significant change. Hip flexed by 59.4° and 19.3° on average at the top and bottom positions, respectively. Minimum liner-to-neck distance was 8.8 mm on average at the bottom position. Liner-to-neck, bone-to-bone, or bone-to-component impingement was not observed at any positions in any hips. Simulation analysis of cup placement showed that larger cup anteversion, inclination, and use of elevated liner significantly decreased the minimum distance between posterior liner and stem neck. Cup anteversion of more than 30° with elevated liner could cause posterior liner-to-neck impingement at bottom position. Interpretation: Stationary cycling after THA provides no excessive hip range of motion or liner-to-neck contact. Cup placement and use of elevated liner significantly influence the minimum liner-to-neck distance, in some cases simulating posterior prosthetic impingement. Highlights: Replaced hip kinematics during cycling were analyzed using image-matching techniques. Optimal cup positioning against prosthetic impingement was simulated using in-vivo kinematics. Stationary cycling provides no excessive replaced hip range of motion or prosthetic contact. Cup placement and use of elevated liner significantly influence the liner-to-neck distance.